Antibacterial and antiproliferative activities of the fresh leaf essential oil of Psidium guajava L. (Myrtaceae) - E. A. J. Silva (Brazilian Journal of Biology, 2018)
Abstract This study evaluated the antibacterial and antiproliferative activities of the essential oil of Psidium guajava leaves (PG-EO), traditionally used in folk medicine. The essential oil was obtained from fresh leaves by hydrodistillation, using a modified Clevenger apparatus. The major PG-EO chemical constituents were identified by GC-MS and GC-FID as being β-caryophyllene (16.1%), α-humulene (11.9%), aromadendrene oxide (14.7%), δ-selinene (13.6%), and selin-11-en-4α-ol (12.5%). The antibacterial activity of the essential oil of P. guajava leaves was determined in terms of its minimum inhibitory concentrations (MIC) using the broth microdilution method in 96-well microplates. PG-EO had moderate activity against Streptococcus mutans (MIC = 200 µg/mL), S. mitis (MIC = 200 µg/mL), S. sanguinis (MIC = 400 µg/mL), S. sobrinus (MIC = 100 µg/mL), and S. salivarius (MIC = 200 µg/mL). The antiproliferative activity was evaluated against different tumor cell lines: breast adenocarcinoma (MCF-7), human cervical adenocarcinoma (HeLa), and human gliobastoma (M059J). A normal human cell line (GM07492A, lung fibroblasts) was included. The antiproliferative activity was evaluated using the XTT assay and the results were expressed as IC50. The essential oil showed significantly lower IC50 values against MCF-7 and M059J lines than that obtained for the normal line, showing selectivity. Our results suggest that the essential oil of Psidium guajava L. has promising biological activities and can be considered a new source of bioactive compounds.